Reconstructing the Concept of Sulh as a Restorative Justice Model in Contemporary Islamic Criminal Law - Mardia Pulungan; Arian Denopan Lubis; Nedi Rinaldi; Muhammad Ilyas (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The growing adoption of restorative justice in contemporary criminal justice systems has intensified scholarly interest in dispute resolution models that are humane, participatory, and oriented toward repairing harm. Within Islamic criminal law, ṣulḥ constitutes a conflict resolution mechanism that shares substantial conceptual affinities with restorative justice; however, its reconstruction as a contemporary restorative justice model remains insufficiently examined. This study aims to analyze the concept of ṣulḥ in Islamic criminal law, identify its relevance to restorative justice, and reconstruct its application in accordance with the requirements of modern criminal justice systems. Employing a qualitative library research approach, the study draws on the Qur’an, Hadith, classical Islamic jurisprudential literature, scholarly books, journal articles, and other relevant academic sources. The data were analyzed through content analysis and a descriptive-analytical framework grounded in maqāṣid al-sharīʿah. The findings demonstrate that ṣulḥ incorporates the principal elements of restorative justice, including dialogue, reconciliation, forgiveness, victim restitution, offender accountability, and the restoration of social relationships. Its contemporary reconstruction may be pursued by strengthening victims’ participation, optimizing penal mediation, and integrating considerations of public welfare (maṣlaḥah) into modern criminal justice practices. The study concludes that ṣulḥ has substantial potential to serve as a restorative justice model in contemporary Islamic criminal law by integrating Islamic legal principles with modern approaches to justice centered on peacebuilding, harm reparation, and social restoration. These findings contribute to Islamic criminal law scholarship by providing a conceptual framework for adapting classical reconciliation mechanisms to contemporary criminal justice contexts.